1986
DOI: 10.1128/jb.165.2.585-594.1986
|View full text |Cite
|
Sign up to set email alerts
|

Siderophores and outer membrane proteins of antagonistic, plant-growth-stimulating, root-colonizing Pseudomonas spp

Abstract: As an approach to understanding the molecular basis of the reduction in plant yield depression by root-colonizing Pseudomonas spp. and especially of the role of the bacterial cell surfaces in this process, we characterized 30 plant-root-colonizing Pseudomonas spp. with respect to siderophore production, antagonistic activity, plasmid content, and sodium dodecyl sulphate-polyacrylamide gel electrophoresis patterns of their cell envelope proteins. The results showed that all strains produce hydroxamate-type side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
0
3

Year Published

1988
1988
2000
2000

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(87 citation statements)
references
References 37 publications
2
82
0
3
Order By: Relevance
“…It has already been demonstrated that for R meliloti 1021 siderophore production is not essential for nodule formation and nitrogen fixation, although it may significantly increase the efficiency of this process (14). Siderophore-mediated competition for iron in microbial systems appears to be a widespread phenomenon (5,(8)(9)(10)41), and it therefore seems likely that siderophores produced by Rhizobium strains could play a role in competition in a manner similar to that of siderophores in the pseudomonads. It Finally, the results presented here strongly indicate that in Rhizobium spp.…”
Section: Resultsmentioning
confidence: 99%
“…It has already been demonstrated that for R meliloti 1021 siderophore production is not essential for nodule formation and nitrogen fixation, although it may significantly increase the efficiency of this process (14). Siderophore-mediated competition for iron in microbial systems appears to be a widespread phenomenon (5,(8)(9)(10)41), and it therefore seems likely that siderophores produced by Rhizobium strains could play a role in competition in a manner similar to that of siderophores in the pseudomonads. It Finally, the results presented here strongly indicate that in Rhizobium spp.…”
Section: Resultsmentioning
confidence: 99%
“…Upon iron limitation new large outer membrane proteins with apparent molecular weights (MWs) between 70,000 and 100,000 are synthesized by fluorescent pseudomonads (8,11,20,24). The presence of such iron-regulated proteins in the outer membrane suggests that they are involved in high-affinity siderophore-mediated Fe3" uptake (26).…”
mentioning
confidence: 99%
“…Their structures consist of a fluorescent chromophore, a dihydroxyquinoline moiety linked to an oligopeptide 5 to 10 amino acids long. They differ mainly in amino acid composition and sequence (7,9,22,28).Rhizosphere-colonizing Pseudomonas putida WCS358 (16) Upon iron limitation new large outer membrane proteins with apparent molecular weights (MWs) between 70,000 and 100,000 are synthesized by fluorescent pseudomonads (8,11, 20,24 Construction of a gene bank. A partial Sau3A digest of genomic WCS358 DNA was fractionated as described previously (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High-molecular-weight iron-regulated proteins (80K to 88K) have been identified in the Pseudomonas fluorescens-related strain B10 (38,39). Large iron-regulated proteins have also been demonstrated in the outer membranes of various root-colonizing strains of fluorescent pseudomonads (18), in Pseudomonas aeruginosa PAO1 (48), and in Pseudomonas syringae pv. syringae (17).…”
Section: Discussionmentioning
confidence: 99%